Spectrum of Meaning in The Architecture of Catholic Church - Salura, Purnama (International Journal of Engineering and Technology, 2018)
This study aims to describe all the relationships between the architecture of the Catholic Church and its meaning. The method used for this research are: First, described the building based on the theory about the scope of the building. Second, interpreted the meaning which is created, both on the exterior and in the interior which is based on the theory of semiotics. The results of the analysis showed that the Salib Suci Church was dominated by indexical and iconic sign, while in Bunda Pemersatu Church, all of the architectural composition as well as its elements was tend to be symbolical which specifically expresses Catholic values. This research contributes to the development of scientific architecture, namely by providing an understanding of the study of semiotics in reading the architecture of the Catholic Church. The research also produced methods to interpret the expression of architectural form in general and specifically on the architec-ture of Catholic Church. The benefit for practice is that this understanding can be the basis for designing Church architecture. As for the stakeholders, this research can be a source of knowledge about the architecture of the Catholic Church which is in line with Catholic values.